DA’WAH STRATEGY USTADZ SYAMSUDDIN NUR MAKKA IN TIK TOK ACCOUNT @SYAM_ELMARUSY - Islamuvida, Zulaytifatul (QAULAN: Journal of Islamic Communication, 2023)
Tik Tok has become one of the social media that is widely used by the community, and is used by some  da'is in delivering their da'wah. Ustadz Syamsuddin Nur Makka became one of the preachers who used Tik Tok as a medium for da'wah. This study aims to analyze the da'wah strategy used by the Sham ustad in delivering da'wah through Tik Tok and to determine the effectiveness of the Sham ustad da'wah through Tik Tok media to the community. The method used is a descriptive qualitative method with data collection techniques in the form of observation and documentation. The results showed that the da'wah strategy used by the Sham ustadz was da'wah bil oral, dakwah bil qalam, and dakwah bil hal. The @syam_elmarusy account brings content with slang and is easy to understand by the audience, brings interesting themes, and interspersed with humor and modern dressing styles like the younger generation today has succeeded in attracting viewers to continue watching @syam_elmarusy account content. Factors that prove the effectiveness of da'wah on @syam_elmarusy account are: first, can be seen from the high viewers on @syam_elmarusy account, this shows that the da'wah delivered by the Sham ustadz attracts the interest of the public.  Second, the large number of comments on @syam_elmarusy account can also prove, if there is feedback from mad'u on the da'wah process carried out by the ustadz Sham.